Leadership Styles, Self-Efficacy, and Innovative Work Behaviour of Software Developers - Kyaw, Win Moe Moe; Soe, Aye Thanda (UI Scholars Hub, 2024)
Research Aims: The primary aims of this study involve examining the effect of leadership styles on self-efficacy and the effect of self-efficacy on innovative work behaviour. Design/Methodology/Approach: Quantitative research was conducted by collecting data from 242 randomly selected software developers in four software development companies in Yangon using structured questionnaires. Regression analysis was used to attain the research objectives. Research Findings: The results showed that transactional and ambidextrous leadership styles have a significant effect on increasing the self-efficacy of software developers. This study also revealed that self-efficacy is an antecedent of the innovative work behaviour of software developers. Theoretical Contribution/Originality: The study confirmed that transactional leadership significantly impacts self-efficacy and validated the role of ambidextrous leadership in self-efficacy. Moreover, self-efficacy was found to have an impact on innovative work behaviour. Managerial Implication in the South East Asian Context: This study suggests that transactional and ambidextrous leadership styles can create enabling environments by encouraging and empowering team members to increase their self-efficacy and engage in more innovative endeavours. Research Limitation & Implications: Data was collected once using a questionnaire from a sample of four companies. The insights can help leaders maintain a sustainable competitive advantage, leading to more job opportunities and long-term economic growth in Myanmar and other developing countries.